Impacts of Urbanisation on the Traditional Medicine of Ethiopia - Wondwosen Teshome-Bahiru (Anthropologist, 8(1): 43-52 (2005), 2005)
The aim of this article is to assess how urbanisation affected the traditional medicine of Ethiopia. The data were collected in Addis Ababa, Ethiopia from June 1998 to January 1999 by employing anthropological techniques of data collection, namely, participant observation and interview. It is found out that the urbanisation process of the country has both positive and negative impacts on the traditional medicine of Ethiopia